ANALISIS PEMBENTUKAN DISONANSI KOGNITIF KONSUMEN PEMILIK MOBIL TOYOTA YARIS - Andrestiawan (2012)
This study attempts to look at the formation of Cognitive Dissonance consumers when they decide to buy a Toyota Yaris, Cognitive Dissonance has three dimensions, namely, emotional, wisdom of purchase, concern over the deal. Emotional terms of despair, regret, disappointment with self, fear, emptiness, anger, anxiety or worry, have made something wrong, annoyed or irritated, frustrated, hurt, depressed, angry with myself, disgusted and got into trouble. Wisdom of Purchase in terms of the dire need of a Toyota Yaris, need to buy a Yaris, has made the right choice, has done the right thing to buy a Toyota Yaris while Concern over the deal do not feel you've done a folly. Using factor analysis results of the research led to three major factors, namely forming dissonance: the right choice, as needed, appropriate approvals.